Pemanfaatan Augmented Reality Sebagai Media Pengenalan Atribut TNI Angkatan Darat Berbasis Android - Rachmat Edy; Haida Dafitri; Septiana Dewi Andriana (Journal of Information System Research (JOSH), 2022)
Augmented Reality is an activity that combines the appearance of virtual and real objects (objects) in real life and at that time will also display 3D objects that we want to see in real time. The process of combining virtual and real objects using technology that continues to develop rapidly in the world of design, interactivity is aimed at the input devices needed to support the goals to be achieved. Augmented reality technology at the Indonesian Army Attributes application is an application that uses the Markerless method with the Pattern Matching technique to display augmented reality 3D objects at the Indonesian Army Attributes. This application system can help users, especially prospective students (cassis) to make it easier for prospective students (casis) to achieve their goals of becoming an Indonesian Army Soldier, starting from the recruitment level and selection of units on duty. This technology can guide users to directly view 3D Indonesian Army Attributes objects without having to browse, not to mention network constraints when accessed, which takes longer. This application system is based on Android and can be accessed and used offline.